ANALISIS GAYA MENGAJAR DOSEN TERHADAP KEHADIRAN MAHASISWA DI UNIVERSITAS BHAYANGKARA JAKARTA RAYA - Arfian; Annanda Vita Nova; Shinda Zahra Gelista; Wulan Febianty; Zalfaa Hafiz Anabresta (CV. ADIBA AISHA AMIRA, 2024)
This study aims to understand the relationship between lecturers’ teaching style and student attendance at Bhayangkara University Jakarta Raya. The subjects in this study were 4 students. The selection of research subjects was carried out using a qualitative method involving active students at Bhayangkara University of Greater Jakarta, 2020-2023 year group. The data collection method uses a scale of lecturer’s teaching style on student attendance. The data analysis method uses a correlational study analysis in the form of an Interview. Based on data analysis, the correlation result of 90% means that there is a negative relationship between the lecturer’s teaching style on student attendance at Bhayangkara University Jakarta Raya. The more positive the lecturer’s teaching style, the greater the student attendance tends to be.